Intracranial haemorrhages associated with venom induced consumption coagulopathy in Australian snakebites (ASP-21). (August 2015) - Berling, Ingrid; Brown, Simon G.A.; Miteff, Ferdi; Levi, Christopher; Isbister, Geoffrey K.
Abstract: Intracranial haemorrhage (ICH) is a rare life-threatening consequence of venom induced consumption coagulopathy in snake-bite. It is unclear why certain patients haemorrhage. We aimed to investigate ICH in snake envenoming. Cases of venom-induced consumption coagulopathy from July 2005–June 2014 were identified from the Australian Snakebite Project, a prospective multicentre cohort of snake-bites. Cases with venom-induced consumption coagulopathy were extracted with data on the snake-bite, clinical effects, laboratory investigations, treatment and outcomes. 552 cases had venom-induced consumption coagulopathy; median age, 40 y (2–87 y), 417 (76%) males, 253 (46%) from brown snakes and 17 died (3%). There were 6/552 (1%) cases of ICH; median age, 71 y (59–80 y), three males and five from brown snakes. All received antivenom and five died. All six had a history of hypertension. Time to onset of clinical effects consistent with ICH was 8–12 h in four cases, and within 3 h in two. Difficult to manage hypertension and vomiting were common. One patient had a normal cerebral CT on presentation and after the onset of focal neurological effects a repeat CT showed an ICH. ICH is rare in snake-bite with only 1% of patients with coagulopathy developing one. Older age and hypertension were associated with ICH. Highlights: Intracranial haemorrhage rarely occurs with venom induced consumption coagulopathy. Intracranial haemorrhage from snakebite is often fatal. Older age and hypertension are associated with intracranial haemorrhage in snakebite.